2021
DOI: 10.1111/bjhp.12534
|View full text |Cite
|
Sign up to set email alerts
|

Stigma is associated with illness self‐concept in individuals with concealable chronic illnesses

Abstract: Objectives. Previous research suggests that chronic illnesses can elicit stigma, even when those illnesses are concealable. Such stigmatization is assumed to lead to a stigmatized identity. Additionally, chronic illness affects one's self-concept, as one reconstructs a sense of self with illness incorporated. However, no research has examined the interplay between stigma and self-concept in those with concealable chronic illnesses. Therefore, we investigated the extent to which experienced, anticipated, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
29
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 60 publications
5
29
0
1
Order By: Relevance
“…Previous work on chronic illness has theorised that these experiences of illness related stigma may reduce well-being via a reconstruction of an individual's identity with both illness and stigma incorporated. 33 Our findings identified the relevance of relapsing-remitting disease trajectories as important drivers of negative mental states because of related uncertainty about the future, which is well-established as a driver of anxiety and depression for people with various chronic diseases. 34 Other research, particularly from earlier on in the pandemic, also identified various barriers to healthcare, 1,14,22,31 including a lack of specialist service provision and limited understanding of the illness from healthcare professionals.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Previous work on chronic illness has theorised that these experiences of illness related stigma may reduce well-being via a reconstruction of an individual's identity with both illness and stigma incorporated. 33 Our findings identified the relevance of relapsing-remitting disease trajectories as important drivers of negative mental states because of related uncertainty about the future, which is well-established as a driver of anxiety and depression for people with various chronic diseases. 34 Other research, particularly from earlier on in the pandemic, also identified various barriers to healthcare, 1,14,22,31 including a lack of specialist service provision and limited understanding of the illness from healthcare professionals.…”
Section: Discussionmentioning
confidence: 65%
“…Previous work on chronic illness has theorised that these experiences of illness related stigma may reduce well-being via a reconstruction of an individual's identity with both illness and stigma incorporated. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, unexamined variables—such as the level of identification with a CHC, visibility, concealability, and broader assessment of accessibility of the educational environment (e.g., resources and skills in navigating online courses)—may also be significantly associated with stigma constructs, academic performance, and health measurements used in the present study. For example, recent work has demonstrated that greater identification with concealable CHCs could exacerbate stigma-related processes (e.g., being vigilant for stigma-related cues and internalization of negative stereotypes; O’Donnell & Habenicht, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Royster and Marshall (2008) state that students with physical CHCs "face specific issues such as : : : unpredictable relapses during the term, and the invisibility of their illnesses, which can make them the subject to disbelief and claims of malingering" (p. 121). Taken together, students with either physical or mental CHCs have reported experiencing stigmas, despite how physical or mental CHCs can be concealed (O'Donnell & Habenicht, 2022;Reinka et al, 2020). Given the increased online instruction in the wake of the COVID-19 pandemic, it is likely that fewer students' CHCs are recognized by educational staff, faculty, and classmates.…”
mentioning
confidence: 99%
See 1 more Smart Citation